Design of Web-Based Helpdesk Ticketing System at PT DENSO Indonesia - Eduard Pangestu Wonohardjo; Annan Hutomo Putra; Emny Harna Yossy (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2022)
PT DENSO Indonesia currently has a helpdesk ticket system based on IBM Lotus Notes. The system is currently not being used optimally because it has limited features, depends on the platform provider, and the source code is difficult to develop. The company has also taken a policy this year not to continue the subscription process to the platform provider. The purpose of this study is to analyze the current business processes and propose a new system model that is computerized, as needed, reliable, and does not depend on a particular platform. The system was developed based on a website using the Extreme Programming (XP) method as a Software Development Life Cycle (SDLC), Unified Model Language (UML) notation as document design, and calculation of completion rate and time-based efficiency in measuring system effectiveness and efficiency. The website-based helpdesk ticketing system was successfully implemented as a new system model that runs independently and has easy-to-develop source code. The system also has a completion rate of 86% and a time-based efficiency of 0.00924 goal/sec based on a problem reporting scenario with 15 participants.